2018
DOI: 10.1097/nne.0000000000000629
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Mindfulness Among Ethnic Minority Undergraduate Nursing Students

Abstract: This paper is NOT THE PUBLISHED VERSION; but the author's final, peer-reviewed manuscript. The published version may be accessed by following the link in th citation below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…Four studies were cross-sectional [18][19][20][21] and 10 were qualitative studies. [22][23][24][25][26][27][28][29][30][31] Characteristics of included studies are presented in Supplemental Digital Content Table 2 (available at: http://links.lww.com/NE/B56). The study samples ranged from 10 28 to 2250 participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies were cross-sectional [18][19][20][21] and 10 were qualitative studies. [22][23][24][25][26][27][28][29][30][31] Characteristics of included studies are presented in Supplemental Digital Content Table 2 (available at: http://links.lww.com/NE/B56). The study samples ranged from 10 28 to 2250 participants.…”
Section: Resultsmentioning
confidence: 99%
“…20 Two studies assessed a sample of only Black students, 23,30 7 studies examined a sample of only Hispanic/Latinx students, 18,21,22,24,26,28,29 and the remaining 5 studies included samples of different combinations of racial/ethnic URM groups. 19,20,25,27,31 Of the 14 included studies, 1 was published in 1999 23 while the remaining 13 were published between 2007 and 2020. [18][19][20][21][22][24][25][26][27][28][29][30][31] Eleven studies included only baccalaureate degree students, 18,19,[22][23][24][25][27][28][29][30][31] 1 study included a sample of baccalaureate and associate degree students, 26 and the remaining 2 studies included a combination of baccalaureate and master's degree students.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The work here not only builds on previous research with the MBC program but offers important findings for a growing body of qualitative inquiry regarding students experience within mindfulness training more broadly. Qualitative explorations of MBPs and health among college students remain understudied and are limited to investigations conducted primarily in specific programs medical, nursing and other health singular academic programs limiting the transferability of results to mixed academic samples [24,[45][46][47][48][49][50][51]. However, some encouraging points should be noted: research has found that students believe mindfulness training enhances individual level resources (i.e., present moment awareness, attention control, self-regulation, self-compassion), increases their ability to balance stress and other academic priorities with purposeful action to enhance well-being (i.e., techniques to cognitively reframe when faced with academic induced anxiety and depression), and increases their self-reported empathy and communication skills in clinical training environments [24,45,48,51,52].…”
Section: Discussionmentioning
confidence: 99%